Comparable immune escape capacity for NB.1 with that of JN.1 variant and survey of infection with severe acute respiratory syndrome coronavirus 2 variants among Chinese Felis silvestris catus - Yuan, Youhua; Geng, Yiman; Zhu, Qiyuan; Sun, Bingfu; Xu, Junhong; Mao, Xiaohuan; Zhang, Xiaohuan; Tian, Wenqian; Zhao, Jing; Zheng, Peiming; Gao, Lan (Frontiers in Immunology, 2026)
BackgroundNeutralising antibodies and infection with the newest severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variant NB.1 in Chinese Felis silvestris catus remains unclear. This study compared the capability of neutralising antibodies in serum against the NB.1 variant prevalent in 2025 with that of the JN.1 variant circulating in 2024 among ill Chinese Felis silvestris catus, and determined whether they could be infected with SARS-CoV-2 variants.MethodsA total of 392 serum samples from ill cats were subjected to enzyme-linked immunosorbent assay (ELISA) to detect the concentration of total antibodies against the receptor-binding domain of SARS-CoV-2; 40 serum samples screened positive by ELISA were subjected to pseudovirus neutralisation test to detect the titres of neutralising antibodies against the JN.1 and NB.1 variants, and 132 throat swab samples from ill cats were screened using specific reverse transcription polymerase chain reaction.ResultsThe geometric mean neutralising titres against the total, NB.1, and JN.1 Omicron variants were 9.51 (95% confidence interval: 7.34–12.3), 24.26 (18.84–31.23), and 48.79 (36.51–65.21) among 40 serum samples from ill cats, respectively. Therefore, neutralisation assays against JN.1 and NB.1 indicated 5.1- and 2.6-fold reductions in neutralising antibody titres, respectively, compared with the total antibody. Additionally, NB.1 showed a 2.91-fold reduction in neutralising antibody titres compared with JN.1. None of the throat swabs from the 132 ill cats were found to be infected with SARS-CoV-2 variants.ConclusionsNB.1 showed increased immune escape capacity in serum compared with JN.1 among Chinese Felis silvestris catus, suggesting that researchers should include the NB.1 antigen in COVID-19 vaccine candidates.